Electron and ion acceleration from femtosecond laser-plasma peeler scheme. (1st March 2023) - Shen, X F; Pukhov, A; Qiao, B
Abstract: Using three-dimensional particle-in-cell simulations, we further investigate the electron and ion acceleration from femtosecond laser–plasma peeler scheme which was proposed in our recent paper (Shen et al 2021 Phys. Rev. X 11 041002). In addition to the standard setup where a laser pulse impinges on an edge of a single tape target, two new variants of the target, i.e. a parallel tape and a cross tape target, were proposed, where strong surface plasma waves can also be efficiently excited at the front edges of the target. By using a tabletop 200 TW-class laser pulse, we observe generation of high-flux, well-collimated, superponderomotive electrons. More importantly, quasimonoenergetic proton beams can always be obtained in all the three setups, while with the single tape case, the obtained proton beam has the highest peak energy and narrowest spectrum.